2012
DOI: 10.1016/j.transproceed.2012.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Study of Heparin in Intestinal Ischemia and Reperfusion in Rats: Morphologic and Functional Evaluation

Abstract: To study whether treatment with heparin (HEP) attenuates intestinal dysfunction caused by ischemia (I) and reperfusion (R), rats were treated with HEP (100 U/kg intravenously) or saline solution (SS) before I (60 min), which was produced by occlusion of the superior mesenteric artery, and R (120 min). After I or I/R, we mounted 2-cm jejunal segment in an organ bath to study neurogenic contractions stimulated by electrical pulses or KCl, using a digital recording system. Thin jejunal slices were stained with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Heparin administration has been demonstrated to limit IR injury to the kidney, intestine, nervous system, pancreas, lungs, liver and heart (Yagmurdur et al ., ; Mocco et al ., ; Taha et al ., ; Yurtcu et al ., ; Gedik et al ., ; Ghadie et al ., ; Warzecha et al ., ), leading us to hypothesise that heparin would have similar protective effects in testicular torsion injury. Our results demonstrate that heparin administration is associated with reduced PC and MDA accumulation in the ipsilateral testicle relative to untreated torsion–detorsion injury.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Heparin administration has been demonstrated to limit IR injury to the kidney, intestine, nervous system, pancreas, lungs, liver and heart (Yagmurdur et al ., ; Mocco et al ., ; Taha et al ., ; Yurtcu et al ., ; Gedik et al ., ; Ghadie et al ., ; Warzecha et al ., ), leading us to hypothesise that heparin would have similar protective effects in testicular torsion injury. Our results demonstrate that heparin administration is associated with reduced PC and MDA accumulation in the ipsilateral testicle relative to untreated torsion–detorsion injury.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated that antioxidant enzymes and ROS‐scavenging compounds can prevent IR injury in experimental testicular torsion (Yagmurdur et al ., ; Can et al ., ; Dokmeci et al ., ; Mocco et al ., ; Taha et al ., ; Yurtcu et al ., ; Wei et al ., ; Gedik et al ., ; Ghadie et al ., ; Warzecha et al ., ; Zavras et al ., ). The effective compounds include polyethylene glycol, ginkgo biloba extract, sildenafil, selenium, taurine and Ca 2+ ‐channel blockers, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin, that is recognised as unfractionated heparin, is a medication that is used as an anticoagulant to treat heart attacks and unstable angina (Boettcher et al, 2016). Previous studies have proved the beneficial impacts of heparin on I/R damage in different body organs such as lungs, heart, liver, pancreas and body systems containing gastrointestinal and urogenital (Gedik et al, 2012;Ghadie et al, 2012;Mocco et al, 2007;Taha et al, 2009;Warzecha et al, 2012;Yagmurdur et al, 2003). Heparin can reduce the accumulation of protein carbonyl and malondialdehyde in the untreated twisted testicle.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] The molecular disturbance produced in cold-ischemia is caused by the excessive production of pro-inflammatory molecules and free radicals. The injuries caused by ischemia are reflecting upon the mitochondrial activity, decreasing the energetic status for a prolonged time.…”
mentioning
confidence: 99%